RESTORATIVE JUSTICE DAN PROSPEKNYA DALAM SISTEM PERADILAN PIDANA, PIDANA ANAK DI INDONESIA - Dwi Afrimetty Timoera (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2014)
Protection of child criminals is important, because children are the future generation in the future. Although so far there are various legal devices, the reality is not quite good enough to bring change for children who have problems with law. Because it needs a diversion in the form of discretion, in the form of a model of restorative justice (restorative justice), in juvenile justice, to avoid psychological trauma and label / stamp former criminals. Kadilan restorative (restorative justice) is expected to be an alternative treatment delinkuensi problem child. The ultimate objective of the concept of restorative justice is expecting a reduction in the number of children who were arrested, detained, and sentenced to prison; eliminate stigma / stamp and return the child to be normal and is expected to be useful later in life